Diagnostic accuracy of the online Patient Health Questionnaire-9 and its abbreviated versions, the PHQ-8 and PHQ-2, for detecting major depressive disorder: research paper - Thake, Moritz; Sikorski, Franziska; Löwe, Bernd; Kohlmann, Sebastian (Journal of affective disorders, 2025)
Background - The Patient Health Questionnaire-9 (PHQ-9) and its abbreviated versions, the PHQ-8 and the PHQ-2, are frequently used as online depression screeners. Their accuracy to detect major depressive disorder (MDD) has been examined in only a limited number of studies in student samples. - Objective - Assessment of the diagnostic accuracy of PHQ-9, PHQ-8 and PHQ-2 to detect MDD. - Methods - A general online population sample was recruited through traditional and social media campaigns, print advertisement in public areas of several German cities and via a nationwide online access survey panel. Participants, aged 18 years or above, completed the PHQ-9 online and were assessed for MDD via telephone using the Structured Clinical Interview for DSM-5 Disorders. Sensitivity, specificity, positive (PPV) and negative (NPV) predictive values, and the area under the curve (AUC) were calculated in a cross-sectional design to assess diagnostic accuracy. - Results - In total, n = 790 participants (574 (72.7 %) female, age: 37.4 (SD = 13.9; range: 18-79)) were screened with the PHQ-9 (mean = 11.1; SD = 5.4) and interviewed via telephone using the SCID (41.2 % fulfilling the criterion of MDD). The optimal cut-off was 11 points for the PHQ-9 (sensitivity: 0.77; specificity: 0.68; AUC: 0.80; NPV: 0.81; PPV: 0.63), 11 points for the PHQ-8 (sensitivity: 0.74; specificity: 0.71; AUC: 0.79; NPV: 0.79; PPV: 0.64) and 3 points for the PHQ-2 (sensitivity: 0.68; specificity: 0.74; AUC: 0.76; NPV: 0.77; PPV: 0.65). Descriptively, age or gender had limited impact on diagnostic accuracy. - Conclusions - In conclusion, the online version of the PHQ-9, PHQ-8, and PHQ-2 show moderate to good diagnostic accuracy to detect MDD. Still, screening results should be interpreted with caution as a number of cases are likely to be either missed or incorrectly identified.